2012
DOI: 10.3389/fimmu.2012.00116
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Signaling in Liver Fibrogenesis

Abstract: Liver fibrosis is the final common pathway of chronic liver diseases irrespective of etiology. However, etiology deeply impacts progression and characteristics of liver fibrogenesis. IL-13 is the dominant pro-fibrotic cytokine in Schistosomiasis associated liver fibrogenesis. In vitro, IL-13 directly induces expression of fibrosis-associated genes, e.g., collagens or connective tissue growth factor, in hepatic stellate cells. Recently, potential effects of IL-13 in non-Schistosomiasis associated liver fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 79 publications
3
76
0
4
Order By: Relevance
“…Similar to other cell types, IL-25 induced secretion of IL-13 by aPFs, but did not further their activation. IL-13 has been implicated in pathogenesis of Schistosoma mansoni infection-induced liver fibrosis (70), and recently IL-13 was shown to directly stimulate HSCs to produce CTGF and subsequently upegulate fibrogenic genes in response to nonparasite liver injury (71). Therefore, we hypothesized that following BDL, IL-25-stimulated aPFs secrete IL-13, which facilitates HSC activation (via induction of IL-13Ra2, Col1a1, Eotaxin, Tenascin-C, fibronection, and phosphorylation of ERK1/ 2).…”
Section: Ahscs and Apfs Contribute Differently To Liver Fibrosis Of Dmentioning
confidence: 99%
“…Similar to other cell types, IL-25 induced secretion of IL-13 by aPFs, but did not further their activation. IL-13 has been implicated in pathogenesis of Schistosoma mansoni infection-induced liver fibrosis (70), and recently IL-13 was shown to directly stimulate HSCs to produce CTGF and subsequently upegulate fibrogenic genes in response to nonparasite liver injury (71). Therefore, we hypothesized that following BDL, IL-25-stimulated aPFs secrete IL-13, which facilitates HSC activation (via induction of IL-13Ra2, Col1a1, Eotaxin, Tenascin-C, fibronection, and phosphorylation of ERK1/ 2).…”
Section: Ahscs and Apfs Contribute Differently To Liver Fibrosis Of Dmentioning
confidence: 99%
“…In our research, it can be found that cori1agin extraction has an effect on granuloma formation, liver cell denaturation, inflammatory cell infiltration and connective tissue, which indicate the collagen proliferation is decreased by corilagin intervention. It has been found that IL-13, a Th2 cytokine, is a crucial pre-fibrosis factor in schistosoma egg-induced hepatic fibrosis (30,31 of responses drives the activation of hepatic stellate cells into a myofibroblast-like phenotype, and then collagen and other extracellular matrix (ECM) components are deposited (32). In this research, we found that corilagin extraction could reduce the level of IL-13 in the liver, which showed corilagin had a potential for anti-fibrosis via IL-13 signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…IL-25 binds to IL-17RA and IL-17RB heterodimers (of which IL-17RB represents an IL-25 specific moiety 85,86 ), and induces Act1-dependent activation of NFκB signaling pathway in target cells 87 . IL-25 drives the expression of IL-13 88 , which is required for suppression of Th17 responses 8284,89,90 . We have demonstrated that IL-25 attenuates liver fibrosis in mice, suggesting that IL-25 agonists may become targets for ALD treatment 67 .…”
Section: Evidence Of the Role Of Il-17 Signaling Pathway In Aldmentioning
confidence: 99%